HPTLC PROFILING OF FLAVONOIDS AND GLYCOSIDES IN THE FLOWERS OF CROSSANDRA INFUNDIBULIFORMIS (L.) NEES - JENCY SAM,; JEYA SUNDARA SHARMILA, (International Journal of Pharma and Bio Sciences, 2015)
Plants as such are useful, of which the flowering species contributes one tenth part in finding new drug or the lead molecules. Crossandra infundibuliformis L Nees (Acanthaceae) is a tropical evergreen shrub reported to have some medicinal properties as wound healing, antioxidant, antimicrobial, antiulcer and antisolar activity. Phytoconstitutents of the flower extract is also screened and display the presence of major phytochemicals. Hence the present work is focused on to identify the flavonoids and glycosides present in the methanolic extract of C.infundibuliformis flowers using High Performance Thin Layer Chromatography (HPTLC) method. The HPTLC profile for flavonoids and glycosides identified five flavonoids and four glycosides in the C.infundibuliformis flower extract. Flavonoids, glycosides and combination of both have been used in drug research for many years due to their vast pharmacological application. In future, these compounds could be isolated from the flowers part of this plant and used as lead molecule.